MicroRNA-1285 Might Potentially Regulate OCT4 Gene Expression by Direct Targeting of its Promoter - Ensieh, M. Poursani; Majid, Mehravar; James, E. Trosko (Journal of Evolving Stem Cell Research, 2016)
The human OCT4 gene encodes a transcription factor that maintains pluripotency and self-renewal in Embryonic Stem (ES) cells. This gene generates several known transcripts by alternative promoter and alternative splicing (OCT4A, OCT4B and OCT4B1). Even though OCT4A is the main isoform responsible for stemness properties, several recent controversial studies claimed that this isoform is expressed in cancer cell lines and differentiated cells, in addition to the ES cells. Our in silico studies revealed that OCT4A promoter has a completely match binding site for hsa-miR-1285. This microRNA was detected in the human embryonic stem cells for the first time and further studies showed that miR-1285 can target some tumor suppressor genes,(TSGs), such as p53, and oncogenic genes, such as TGM2. Additional bioinformatics analysis of short RNA sequencing data from ENCODE cell lines showed that miR-1285 is expressed in different cancer cell lines and differentiated cells. In this study, we supposed that miR-1285 potentially can bind to the OCT4 promoter and might regulate transcription of the OCT4 in the human cancer cell lines and differentiated cells.
Keywords: OCT4 gene; OCT4A; microRNA; hsa-miR-1285; cancer cells; promoter.